2014
DOI: 10.3748/wjg.v20.i42.15830
|View full text |Cite
|
Sign up to set email alerts
|

Seroprevalence of celiac disease among United Arab Emirates healthy adult nationals: A gender disparity

Abstract: Compared to men the CD seroprevalence among women was remarkably higher. The CD association with women and chronic anemia is of importance from a public health perspective.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
20
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 33 publications
1
20
0
1
Order By: Relevance
“…Celiac disease is a throughout life disorder caused by ingested cereal-derived gluten in predisposed individuals [3]. Since celiac disease is common but difficult to detect because of the heterogeneous clinical picture, a wide scale screening of the whole population with .The present study also showed that the prevalence of celiac disease was more frequent among females than males, this was compatible with most of the celiac disease epidemiological studies reported by Aljebreen AM, et al, 2013 study [19] and Abu-Zeid YA, et al, 2014 study [16] which concluded that celiac disease affected females more frequently than males. Possibly females are genetically more susceptible to environmental exposure factors that impact the immunological processes and resulting CD [26] because the genetic predisposition HLA DQ2/DQ8, are more recurrent in female compared to male CD patients [27].In conclusion, the high prevalence rate of seropositivity of celiac disease among healthy student individuals and is found in female students more than males.…”
Section: Discussionsupporting
confidence: 87%
“…Celiac disease is a throughout life disorder caused by ingested cereal-derived gluten in predisposed individuals [3]. Since celiac disease is common but difficult to detect because of the heterogeneous clinical picture, a wide scale screening of the whole population with .The present study also showed that the prevalence of celiac disease was more frequent among females than males, this was compatible with most of the celiac disease epidemiological studies reported by Aljebreen AM, et al, 2013 study [19] and Abu-Zeid YA, et al, 2014 study [16] which concluded that celiac disease affected females more frequently than males. Possibly females are genetically more susceptible to environmental exposure factors that impact the immunological processes and resulting CD [26] because the genetic predisposition HLA DQ2/DQ8, are more recurrent in female compared to male CD patients [27].In conclusion, the high prevalence rate of seropositivity of celiac disease among healthy student individuals and is found in female students more than males.…”
Section: Discussionsupporting
confidence: 87%
“…Studies on the prevalence of CD in the general population are available only from seven Asian countries. Although population‐based studies are not available from many Asian countries, the presence of CD has been described in the form of case‐series from China, Iraq, Pakistan, Uzbekistan, Kuwait, Lebanon, Oman, Syria, Taiwan, Singapore, Japan, and United Arab Emirates . In addition, case reports of CD have been published from some other Asian countries such as Bangladesh, South Korea, and Yemen .…”
Section: Discussionmentioning
confidence: 99%
“…Although populationbased studies are not available from many Asian countries, the presence of CD has been described in the form of case-series from China, Iraq, Pakistan, Uzbekistan, Kuwait, Lebanon, Oman, Syria, Taiwan, Singapore, Japan, and United Arab Emirates. 24,25,27,[44][45][46][47][48][49][50][51] In addition, case reports of CD have been published from some other Asian countries such as Bangladesh, South Korea, and Yemen. [52][53][54] There still are no reports on CD from many Asian countries such as Azerbaijan, Kazakhstan, Turkminstan, Afganistan, Kyrgyzstan, Tajikistan, Cambodia, Myanmar, Vietnam, Mongolia, Nepal, and Bhutan.…”
Section: Discussionmentioning
confidence: 99%
“…However, the prevalence in different ethnicities varies. (2) The prevalence of CD among Europeans is thought to be about 1-1.5% (2) with a similar estimated prevalence of about 1.1% in the adult Israeli population (3) and 1.2% in the United Arab Emirates, (4) while the disease appears to be less common in Indonesia, (2) South Korea, (2) and the Philippines (2), which may be related to the lower consumption of wheat in those populations. A retrospective study from the Northern part of India reported a significant increase in the prevalence of CD in the past decade.…”
Section: Introductionmentioning
confidence: 99%